Afforestation improves soil fertility in south-eastern Spain - Serrano, L Rojo; Jime, M N; Ferna, E; Ferna, J; Roca, A; Aguilar, J; Fernandez-Ondono, E; Rojo Serrano, L; Jiménez, M N; Navarro, F B; Diez, M; Martin, F; et al. (EUROPEAN JOURNAL OF FOREST RESEARCH, 2010)
In the 20th century, in the Mediterranean area, many extensive afforestation efforts were made with the primary objective of protecting soils from erosion and improving their fertility. This study evaluates the effects of the afforestation undertaken in the Guadalentin basin (SE Spain) with respect to the organic and inorganic soil constituents and physico-chemical soil properties. Given the phytoclimatic environments in the basin (sclerophyllous and hyperxerophyllous), paired samples were taken beneath the tree canopy of the pine plantations and in nearby open zones. With the same methodology, samples were taken from areas considered to be native forest. The data were submitted to different multivariate analyses of variance (two-way MANOVAs) in order to compare the effects and interactions of the factors CANOPY (with and without trees), PHYTOCLIMATE (sclerophyllous and hyperxerophyllous), and TYPE OF FOREST (afforested or native) on the dependent variables measured (soil variables). Significant differences were found at 0-10 cm in soil depth under pine afforestations in relation to adjacent open areas. Below this depth, differences were found only between phytoclimatic environments. No significant interactions were found between the variables analysed at any of the depths, indicating that the effects of the afforestations on the soil characteristics were independent of the phytoclimatic environment. The afforestation in the Guadalentin basin, in the two phytoclimatic environments considered increased the soil fertility. Nevertheless, the native forests presented the highest soil organic-carbon contents, mainly in the sclerophyllous phytoclimate type (Quercus ilex subsp. ballota forests). Therefore, although the afforestations improved the soil fertility in relation to the open areas, the maximum potential has probably not been reached in relation to that observed in the native forests. The effects that forest development (age, basal area) over time exerts on soil properties remain to be verified by further research.
Keywords: Afforestation; Differential pedological characteristics; Guadalentin basin; organic carbon

INFLUENCIA DE DISTINTOS TRATAMIENTOS CULTURALES EN UNA FORESTACIÓN CON ENCINAS EN AMBIENTE SEMIÁRIDO - Jiménez, M N; Ripoll, M A; Navarro, F B; Gallego, E; De Simón, E (IV Congreso Forestal Español, 2005)
En este trabajo se analizó el efecto que produjeron distintos tratamientos culturales (binas, aplicación de mulches y riegos en distintas épocas del verano) en una forestación con encinas en un terreno agrícola abandonado, situado en el Altiplano del Conejo (Guadix, SE España), localidad donde la encina tiene un límite de distribución natural por excesiva xericidad. Tras cuatro años de seguimiento (2001-2004), todos los tratamientos excepto el aporte de residuos sólidos urbanos presentaron mayor supervivencia y superficie foliar respecto a la parcela testigo. Los mejores resultados se obtuvieron en la parcela que recibió riego estival continuo. Sin embargo, altura y diámetro no mejoraron significativamente con los tratamientos, tan sólo en el caso de riegos continuados. Palabras
Keywords: binas; mulches; quercus ilex subsp. ballota; Riegos; terreno abandonado

Modificación del microclima edáfico producido por riegos en forestaciones de zonas semiáridas - Jiménez, M N; Ripoll, M A; Navarro, F B (Investigación agraria. Sistemas y recursos forestales, 2004)
In this work, we analyse the effect that the irrigation carried out in different times during the summer drought produces on the edaphic microclimate over holm oak plants (Quercus rotundifolia) in abandoned agricultural soils of continental semiarid climate. The study has been done over 5 plots of 60 plants each, located in the high plateaux of Rambla Becerra (Guadix-Granada), in which it has been accomplished a continuation of the survival rate and development after the planting during two years (2001-2002). The answer of the plant to its new medium was excellent in all the irrigated plots, whereas in the witness plot (without irrigation) the survival is considerably inferior. The height of the holm oaks in those plots with any kind of irrigation is significantly superior than the ones in the witness plot, and the diameter of the holm oaks of the plots which receive continuous summer irrigation shows significant differences with respect to the rest of the plots. The bioclimatic diagrams achieved in each plot reflect relevant differences; the summer irrigation reaches to reduce the drought period and even, in the plot that receives the continuous summer irrigation, this is eradicated, thus generating a new period of vegetation activity. The humidity of the soil shows significant differences, being the plot number 8, which is continually being irrigated, the only one that keeps the humidity in depth. The hydric deficit diminishes punctually in the plots irrigated only once, whereas in the parcel n. 8 diminishes drastically with the following increase in the vegetation activity.
Keywords: agricultural; bioclimatic diagrams; humidity; microclimate; Soil

A myco-ecological analysis (lignicolous Aphyllophorales sensu lato, Basidiomycota) of the Abies pinsapo, Quercus and Pinus forests of Andalusia (southern Spain) - Ortega, a.; Navarro, F B (Nova Hedwigia, 2004)
This paper presents a mycological inventory (lignicolous Aphyllophorales) of five substrates that are characteristic of Mediterranean vegetation in Andalusia: Abies pinsapo, Quercus faginea, Quercus ilex subsp. ballota, Quercus suber and Pinus sp. pl. The species richness of each substrate was determined and related to the number of vegetation series to which these tree species belong. A series of parameters were used to determine the myco-ecological relationships in the substrates, namely the level of affinity proposed by Goslee, the level of similarity (Sørensen’s quantitative index) and the level of diversity (degree of alpha diversity). A correspondence analysis was also carried out.
Keywords: affinity.; Mediterranean forests; myco-diversity; similarity